Further Evidence That OPG rs2073618 Is Associated With Increased Risk of Musculoskeletal Symptoms in Patients Receiving Aromatase Inhibitors for Early Breast Cancer - Hertz, Daniel L.; Smith, Karen Lisa; Zong, Yuhua; Gersch, Christina L.; Pesch, Andrea M.; Lehman, Jennifer; Blackford, Amanda L.; Henry, N. Lynn; Kidwell, Kelley M.; Rae, James M.; Stearns, Vered (Frontiers in Genetics, 2021)
Background: Aromatase inhibitors (AI) reduce recurrence and death in patients with early-stage hormone receptor-positive (HR+) breast cancer. Treatment-related toxicities, including AI-induced musculoskeletal symptoms (AIMSS), are common and may lead to early AI discontinuation. The objective of this study was to replicate previously reported associations for candidate germline genetic polymorphisms with AIMSS. Methods: Women with stage 0-III HR+ breast cancer initiating adjuvant AI were enrolled in a prospective clinic-based observational cohort. AIMSS were assessed by patient-reported outcomes (PRO) including the PROMIS pain interference and physical function measures plus the FACT-ES joint pain question at baseline and after 3 and 6 months. For the primary analysis, AIMSS was defined as ≥4 point increase in pain interference T-score from baseline. Secondary AIMSS endpoints were defined as ≥4 point decrease in physical function T-score from baseline and as ≥1 point increase on the FACT-ES joint pain question from baseline. The primary hypothesis was that TCL1A rs11849538 would be associated with AIMSS. Twelve other germline variants in CYP19A1, VDR, PIRC66, OPG, ESR1, CYP27B1, CYP17A1, and RANKL were also analyzed assuming a dominant genetic effect and pre-specified direction of effect on AIMSS using univariate logistic regression with an unadjusted α=0.05. Significant univariate associations in the expected direction were adjusted for age, race, body mass index (BMI), prior taxane and type of AI using multivariable logistic regression. Results: 143 participants with PRO and genetic data were included in this analysis, most of whom were treated with anastrozole (78%) or letrozole (20%). On primary analysis, participants carrying TCL1A rs11849538 were not more likely to develop AIMSS (Odds Ratio=1.29, 95% Confidence Interval: 0.55-3.07, p=0.56). In the statistically uncorrected secondary analysis, OPG rs2073618 was associated with AIMSS defined by worsening on the FACT-ES joint pain question (OR=3.33, p=0.004) and this association maintained significance after covariate adjustment (OR=3.98, p=0.003). Conclusions: Carriers of OPG rs2073618 may be at increased risk of AIMSS. If confirmed in other cohorts, OPG genotyping can be used to identify individuals with HR+ early breast cancer in whom alternate endocrine therapy or interventions to enhance symptom detection and implement strategies to reduce musculoskeletal symptoms may be needed.